Infections in the Era of Targeted Therapies: Mapping the Road Ahead - Calabrese, Leonard H.; Calabrese, Cassandra; Lenfant, Tiphaine; Kirchner, Elizabeth; Strand, Vibeke (Frontiers in Medicine, 2020)
Immunosuppressive treatment strategies for autoimmune diseases have changed drastically with the development of targeted therapies. While targeted therapies have changed the way we manage immune mediated diseases, their use has been attended by a variety of infectious complications – some expected and some unexpected. This perspective examines the lessons learned from the use of different targeted therapies over the past several decades, and reviews the existing strategies to minimize infectious risk. Several of these infectious complications were predictable in light of preclinical models and preliminary clinical studies (i.e. tuberculosis and TNF inhibitors, or meningococcus and eculizumab). While these scenarios can potentially serve us well in terms of enhancing our predictive powers (higher vigilance, earlier detection and risk mitigation), targeted therapies have also revealed unpredictable toxicities (i.e. natalizumab and progressive multifocal leukoencephalopathy). Severe infectious complications, even if rare, can derail a promising therapeutic and highlights the need for increased awareness and meticulous adjudication. Tools are available to help mitigating infectious risk. The first step is to assure that infection safety is adequately studied at every level of drug development prior to and after regulatory approval and that registries collect real-world adverse events in a collaborative effort. The second step is to identify high risk patients (i.e. risk calculators such as RABBIT risk score, big data, artificial intelligence). Finally, the greatest and most underutilized intervention to prevent infections in patients receiving targeted therapies across the spectrum of immune mediated inflammatory diseases are vaccinations.